The Use of Essential Oils and Their Isolated Compounds for the Treatment of Oral Candidiasis: A Literature Review. (8th January 2021) - Ferreira, Elba dos Santos; Rosalen, Pedro Luiz; Benso, Bruna; de Cássia Orlandi Sardi, Janaina; Denny, Carina; Alves de Sousa, Simone; Queiroga Sarmento Guerra, Felipe; de Oliveira Lima, Edeltrudes; Almeida Freires, Irlan; Dias de Castro, Ricardo
Abstract : In this literature review, we present the main scientific findings on the antifungal activity of essential oils (EOs) applicable for a new drug formulation to treat oral candidiasis. Seven literature databases were systematically searched for eligible in vitro and clinical trials. Selected articles were screened for biological activity, botanical species, phytochemical composition, study design, and methodological quality. A total of 26 articles were included in the review, of which 21 were in vitro studies and 5 clinical trials. The most promising EOs were obtained from Allium tubeorosum, Cinnamomum cassia, Cinnamomum zeylanicum, and Coriandrum sativum L. Among the phytochemicals, citral and thymol were the most active. Clinical trials indicated that the EOs from Pelargonium graveolens and Zataria multiflora are potentially effective to treat oral candidiasis. Further nonclinical and clinical studies with these EO are warranted to determine their potential use and safety for the treatment of oral candidiasis.